The ‘Absolute Colour Music’ of Jan van Deene: Inventing Abstraction in Paris 1911-13 - van Halem, Ludo (The Rijksmuseum Bulletin, 2023)
Ludo van Halem discusses the work of Jan van Deene and artists in his network who for the first time in the Netherlands showed a large group of abstract paintings, developed in Paris, at the second jury free exhibition of De Onafhankelijken in 1913. They were reviled in the press, and their contribution was only recognized late. For example, Jan van Deene’s Peinture VII (1913) was only included in the Rijksmuseum collection in 2019.